A Method for Comparing the Fatigue Performance of Forged AZ80 Magnesium - Andrew Gryguć; Seyed Behzad Behravesh; Hamid Jahed; Mary Wells; Bruce Williams; Rudy Gruber; Alex Duquette; Tom Sparrow; Jim Prsa; Xuming Su (Metals, 2021)
A closed die forging process was developed to successfully forge an automotive suspension component from AZ80 Mg at a variety of different forging temperatures (300 °C, 450 °C). The properties of the forged component were compared and contrasted with other research works on forged AZ80 Mg at both an intermediate forging and full-scale component forging level. The monotonic response, as well as the stress and strain-controlled fatigue behaviours, were characterized for the forged materials. Stress, strain and energy-based fatigue data were used as a basis for comparison of the durability performance. The effects of the starting material, forging temperature, forging geometry/configuration were all studied and aided in developing a deeper understanding of the process-structure-properties relationship. In general, there is a larger improvement in the material properties due to forging with cast base material as the microstructural modification which enhances both the strength and ductility is more pronounced. In general, the optimum fatigue properties were achieved by using extruded base-material and forging using a closed-die process at higher strain rates and lower temperatures. The merits and drawbacks of various fatigue damage parameters (FDP’s) were investigated for predicting the fatigue behaviour of die-forged AZ80 Mg components, of those investigated, strain energy density (SED) proved to be the most robust method of comparison.